Effect of pacing strategy on energy expenditure during a 1500-m cycling time trial - Hettinga, F. J.; de Koning, J. J.; Meijer, E.; Teunissen, L.; Foster, C. (Medicine & Science in Sports & Exercise, 2007)
Purpose: A critical assumption in modeling optimal pacing strategy is that the amount of anaerobic energy that can be produced during a time trial is a constant value, independent of pacing strategy. To test this assumption, the effect of manipulations of pacing strategy on anaerobic work produced during a 1500-m cycling time trial was studied. Additionally, the effect of pacing strategy on aerobic and total work was studied.